A Supramolecular Nanoparticle of Pemetrexed Improves the Anti-Tumor Effect by Inhibiting Mitochondrial Energy Metabolism - Liu, Hui; Guo, Chunlei; Shang, Yuhong; Zeng, Lin; Jia, Haixue; Wang, Zhongyan (Frontiers in Bioengineering and Biotechnology, 2021)
In recent years, supramolecular hydrogels consisting of peptides and drugs have been regarded as useful drug delivery systems for tumor therapy. Pemetrexed (PEM) is a multitarget drug that is effective for many cancers, such as non-small cell lung cancer. Here, RGD-conjugated molecular hydrogels mainly composed of an anticancer drug of PEM (PEM-FFRGD) were prepared to deliver PEM to tumors. The peptide could self-assemble into a nanoparticle structure with diameter of about 20 nm. Moreover, the hydrogel showed favorable solubility and biocompatibility compared with those of PEM, and the MTT test on A549 and LLC cells showed that the PEM-FFRGD nanoparticles had stronger cytotoxic activity than PEM alone. Most importantly, the hydrogel could promote tumor apoptosis and decrease mitochondrial energy metabolism in tumors. In vivo studies indicated that PEM-FFRGD nanoparticles had enhanced antitumor efficacy in LLC tumor-bearing mice compared to that of PEM. Our observations suggested that PEM-FFRGD nanoparticles have great practical potential for application in lung cancer therapy.